2018
DOI: 10.1007/s12024-018-9980-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic role of serum tryptase in anaphylactic deaths in forensic medicine: a systematic review and meta-analysis

Abstract: Postmortem diagnosis of sudden death due to anaphylaxis can be very difficult due to the non-specific pathological findings in forensic practice. Postmortem serum tryptase has been used as an indicator of possible ante-mortem anaphylaxis. Though many previous studies have been conducted to explore the diagnostic significance of serum tryptase for lethal anaphylaxis, inconsistent results were documented. In this study, we made a retrospective study and presented a systematic review and meta-analysis that aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The quality assessment of the included studies was conducted with the Newcastle–Ottawa Quality Assessment Scale (NOS), and the studies with NOS scores ≥ 7 were considered to be high-quality studies [63]. The evaluation contents include: (1) Selection of the included studies: ① case definition adequate (the cause of death was diagnosed by at least two independent pathologists according to autopsy findings, histological investigations, and other lab investigations), ② representativeness of the cases, ③ selection of controls, ④ definition of controls (1 point for each item, 4 points in total).…”
Section: Methodsmentioning
confidence: 99%
“…The quality assessment of the included studies was conducted with the Newcastle–Ottawa Quality Assessment Scale (NOS), and the studies with NOS scores ≥ 7 were considered to be high-quality studies [63]. The evaluation contents include: (1) Selection of the included studies: ① case definition adequate (the cause of death was diagnosed by at least two independent pathologists according to autopsy findings, histological investigations, and other lab investigations), ② representativeness of the cases, ③ selection of controls, ④ definition of controls (1 point for each item, 4 points in total).…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noting that older publications (37) (prior to late 1990s) used β MCT as opposed to total (α and β) MCT in the last decade. Sun et al recently published a systematic review and meta-analysis to address this question and concluded that at concentrations >30.4 μg/L, sensitivity and specificity for anaphylaxis were 68.5 and 83.9%, respectively (50).…”
Section: Use Of Serum Mct In Forensic Medicinementioning
confidence: 99%
“…The severe and potentially lethal multi-organ hypersensitivity reaction [17] defined as anaphylactic shock is due to the exposure to a specific allergen [9,18], towards which an immune system sensitization has already developed. The reexposure to the same allergen-type I hypersensitivity IgE antibodies mediated-ultimately causes the degranulation of the mast cells and of the tissue basophils with the release of histamine and other mediators that may cause a precipitous death due to cardio-respiratory arrest [7].…”
Section: Discussionmentioning
confidence: 99%